Augmented Reality Design Heuristics: Designing for Dynamic Interactions. (September 2017) - Endsley, Tristan C.; Sprehn, Kelly A.; Brill, Ryan M.; Ryan, Kimberly J.; Vincent, Emily C.; Martin, James M.
Augmented Reality (AR) has emerged as a rapidly developing technology, capable of a wide scope of applications across a variety of domains. AR technologies allow for a virtual experience to be overlaid on top of a physical environment, creating a hybrid experience in which virtual objects become a part of the user's perceptual and physical environment. Rapid progression of the AR field requires that effective and validated methods of design evaluation be developed. Failure to consider the usability of AR applications during the design process will result in an increase in user errors and accidents, limiting user trust of the technology and undermining user perceptions of the technology, for both AR and Virtual Reality (VR) technologies (Nordrum, 2016). Through a robust and iterative process, a set of Design Heuristics for AR were developed for multidimensional augmented environments with the aim of advancing AR design methods for human factors, ergonomics, and user experience practitioners within the expanding AR community.